Short-term overseas study and cultural adaptation a case study of Vietnamese students in japan, the USA and the philippines = Trao đổi ngắn hạn và hòa nhập văn hóa nghiên cứu cá thể sinh viên Việt Nam ở Nhật Bản, Hoa Kỳ và phi-lip-pin - Phạm, Thị Minh Trang (ĐHQGHN - Trường Đại học Ngoại Ngữ, 2021)
Cross-cultural adaptation has received considerable concern from researchers and educators all over the world. With an investigation into the adaptation process of undergraduate Vietnamese students in different foreign countries, the research aims to examine obstacles as well as strategies experienced by participants and to highlight the affecting factors on their adaptation process. Based on the work of Berry (1996) and Gullahorn & Gullahorn (1963), to achieve that target, the researcher applies qualitative methods with two instruments namely weekly diary and semi-structured interview to collect data from three undergraduate Vietnamese students studying their short term exchange programmes at universities in Japan, the Philippines, and the US. Findings indicates that there is a sign of U-curve model stated by Oberg (1960) in three participants’ adaptation process while overseas; however, the last stage “Adaptation” is not fully reached due to their limited cultural exposure time. Environment, traffic, food, and prices, language, interaction with locals and schooling are the main problems students confronted with. Noticeable strategies employed include behavioural shift, cultural conflict (new culture ignorance), support-seeking from local people; and host nation interaction, among which a shift in their behaviour appears to be the most commonly utilised and effective strategy. Findings also show that moderating factors prior to and during acculturation as well as students’ society of origin considerably influence their adaptation process.